2016
DOI: 10.1371/journal.pone.0168027
|View full text |Cite
|
Sign up to set email alerts
|

Euphorbia Kansui Reactivates Latent HIV

Abstract: While highly active anti-retroviral therapy has greatly improved the lives of HIV infected individuals, these treatments are unable to eradicate the virus. Current approaches to reactivate the virus have been limited by toxicity, lack of an orally available therapy, and limited responses in primary CD4+ T cells and in clinical trials. The PKC agonist ingenol, purified from Euphorbia plants, is a potent T cell activator and reactivates latent HIV. Euphorbia kansui itself has been used for centuries in tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Euphorbia kansui has been used as part of traditional Chinese medicine as a cathartic and contains twelve ingenol compounds(53). Kansui plant extracts have been shown to reactivate HIV-1 in both cell lines in vitro and in patient cells ex vivo (54). Kansui is safe and has oral bioavailability as a tea.…”
Section: Side Effects Of T Cell Activating Agents: Mitigating Pro-infmentioning
confidence: 99%
“…Euphorbia kansui has been used as part of traditional Chinese medicine as a cathartic and contains twelve ingenol compounds(53). Kansui plant extracts have been shown to reactivate HIV-1 in both cell lines in vitro and in patient cells ex vivo (54). Kansui is safe and has oral bioavailability as a tea.…”
Section: Side Effects Of T Cell Activating Agents: Mitigating Pro-infmentioning
confidence: 99%
“…We next sought to test the PKC activity and cytotoxicity of synthetic ingenols in resting CD4 Ï© T cells in vitro as a means to explore the therapeutic windows of these compounds. Cell surface expression of CD69, a biomarker of early T cell activation, is well known to directly correlate with PKC activity (46)(47)(48). Recent studies with bryostatin-1 and bryostatin analogs have demonstrated a direct correlation between CD69 expression and HIV-1 latency reversal in vitro (48,49).…”
Section: Figmentioning
confidence: 99%
“…Therefore, a combination of a P-TEFb-releaser and a PKC agonist elicits a potent induction of HIV transcription in latently infected cells [161,171,274]. Interestingly, extracts from Euphorbia kansui, a plant used in Chinese traditional medicine for treatment of fluid retention, cancer, or ascites, contains a high concentration of various ingenol derivatives, and exhibits potent HIV reactivation in combination with HDACis or BETis [276]. P-TEFb-releasers/activators are also effective as anti-cancer agents.…”
Section: Increasing P-tefb Activitymentioning
confidence: 99%